Assessment of Central Nervous System Lymphoma Based on CXCR4 Expression In Vivo Using 68Ga-Pentixafor PET/MRI. (January 2021) - Starzer, Angelika M.; Berghoff, Anna S.; Traub-Weidinger, Tatjana; Haug, Alexander R.; Widhalm, Georg; Hacker, Marcus; Rausch, Ivo; Preusser, Matthias; Mayerhoefer, Marius E.
Abstract : Purpose of the Report: 18 F-FDG PET is limited for assessment of central nervous system lymphoma (CNSL) due to physiologic tracer accumulation in the brain. We prospectively evaluated the novel PET tracer 68 Ga-pentixafor, which targets the C-X-C chemokine receptor 4 (CXCR4), for lesion visualization and response assessment of CNSL. Materials and Methods: Seven CNSL patients underwent 68 Ga-pentixafor PET/MRI with contrast enhancement (CE-MRI) and diffusion-weighted sequences. The accuracy of 68 Ga-pentixafor PET for CNSL lesion detection relative to the CE-MRI reference standard was determined. Standardized uptake values (SUVmean and SUVmax ), PET-based (PTV) and MRI-based (VOLMRI ) tumor volumes, and apparent diffusion coefficients (ADCs) were assessed, and correlation coefficients were calculated. Three SUVmax thresholds (41%, 50%, and 70%) were evaluated for PTV definitions (PTV41%, PTV50%, and PTV70% ) and tested against VOLMRI using paired sample t tests. Results: Twelve 68 Ga-pentixafor PET/MRI examinations (including 5 follow-up scans) of 7 patients were evaluated. 68 Ga-pentixafor PET demonstrated 18 lesions, all of which were confirmed by CE-MRI; there were no false-positive lesions on PET (accuracy, 100%). PTV41% showed the highest concordance with lesion morphology, with no significant difference compared with VOLMRI (mean difference, −0.24 cm 3 ; P = 0.45). The correlation between ADCmean and SUVmean41% ( r = 0.68) was moderate. Changes in PTV41% on follow-up PET/MRI showed the same trend as VOLMRI changes, including progression of 1 lesion each in patient 1 (+456.0% PTV41% and +350.8% VOLMRI ) and patient 3 (+110.4% PTV41% and +85.1% VOLMRI ). Conclusions: 68 Ga-pentixafor PET may be feasible for assessment and follow-up of CNSL. Future studies need to focus on testing its clinical value to distinguish between glioma and CNSL, and between radiation-induced inflammation and viable residual tumor.